The role of nurses as health educator so patients with Diabetes Mellitus type 2: Integrative review (Research, Society and Development, 2022)
Objetive: To identify and analyze the scientific productions available in the literature on educational actions in health, promoted by nurses to patients with type 2 diabetes mellitus. Methods: is an Integrative Review, conducted from January to March 2022 including scientific articles, selected and published from 2018 to 2022, in Portuguese, English and Spanish in the databases of Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library (SciELO), and the Nursing Database (BDENF). Results: We included 4 articles between 2018 and 2020, all of which were published and carried out in Brazil. Regarding the types of studies, each author used a methodology being these intervention studies, exploratory and descriptive study, descriptive study, and randomized clinical trial. With emphasis on health education provided by nurses to patients with type 2 DM; to show which educational measures were elucidated to the patients; and what benefits are provided with health education. Conclusion: The study made it possible to identify the importance of nurses participation as educators, and gaps in education in health education, and evidenced the impact of work overload for the development of educational activities.